Children's Laughter and Emotion Sharing With Peers and Adults in Preschool - Cekaite, Asta; Andrén, Mats (Frontiers in Psychology, 2019)
The present study investigates how laughter features in the everyday lives of 3-5-year old children in Swedish preschools. It examines and discusses typical laughter patterns and their functions with a particular focus on children’s and intergenerational (child-adult/educator) laughter in early education context. The research questions concern: who laughs with whom; how do adults respond to children’s laughter, and what characterizes the social situations in which laughter is used and reciprocated. Theoretically, the study answers the call for sociocultural approaches that contextualize children’s everyday social interaction, e.g., in different institutions or homes, to study the diverse conditions society forms for learning, sociality and socialization and development of shared norms. Methodologically, the study makes use of mixed methods: it uses descriptive statistics that identify prevalent patterns in laughter practices and, on the basis of these results, examines social-interactional situations of children’s laughter in detail. It was found that children’s laughter tended to be directed to children and adults’ laughter tended to be directed to adults. 87% of children’s laughter was directed to other children, and adults directed their laughter to other adults 2,7 times as often as to children. The qualitative interaction analysis shows that children and adults exhibited different patterns of laughter. Children primarily sought and received affiliation through laughter in the peer group, and the adults were often focused on the institutional and educational goals of the preschool. Overall, the study shows that intergenerational reciprocal laughter was a rare occurrence and suggests that laughter between generations is interesting in that it can be seen as indicative of how children and adults handle alterity in their everyday life. By deploying multiple methods, the present study points to the importance of viewing emotion and norm sharedness in social interaction not just as a matter of communicating an emotion from one person to another, but as an intricate process of inviting the others into or negotiating the common emotional and experiential ground.